JUSTIFICATION OF UNIVERSAL IRON SUPPLEMENTATION FOR INFANTS 6-12 MONTHS IN REGIONS WITH A HIGH PREVALENCE OF THALASSEMIA - Phakatip Sinlapamongkolkul; Pacharapan Surapolchai; Vip Viprakasit (Mediterranean Journal of Hematology and Infectious Diseases)
Introduction: Many clinicians hesitate adopting a universal infant iron supplementation program due to the risk of increased iron absorption for those with thalassemia. We aimed to determine thalassemia prevalence in 6- to 12-month old infants, along with the iron status of those with and without thalassemia.